Lembaga Hisbah dalam Ekonomi Bisnis Islam - Umi Arifah; Nihayatul Baroroh; Siti Muttoharoh (LABATILA : Jurnal Ilmu Ekonomi Islam, 2023)
Hisbah is a religious institution controlled by the government to supervise the community in carrying out their obligations properly with the aim of ensuring the welfare of the community in accordance with God's law. The research was conducted by analyzing hisbah institutions in Islamic business economics. The research method was carried out using a library research approach and data collection was carried out by reviewing, exploring journals, books and other relevant supporting documents. The results of the study show that hisbah is part of Islamic history with the task of monitoring and supervising economic activity practices that are not in accordance with the principles of the Qur'an and Hadith. Hisbah institutions are also tasked with guiding the community to comply with the Al-Qur'an and Hadith and have a role in Islamic business economics. The functions of hisbah institutions are as follows: 1) monitoring the adequacy of goods and services in the market; 2) industrial supervision; 3) service supervision; 4) trade supervision; 5) planning and supervision of cities and markets; 6) overall supervision of the market.